2021
DOI: 10.35741/issn.0258-2724.56.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Flood Monitoring and Warning Systems: A Brief Review

Abstract: Floods and excessive rainfall are unavoidable phenomena that can cause massive loss of people's lives and destruction of infrastructure. Flash floods rise rapidly in flood-prone areas, resulting in property damage, but the impact on human lives is relatively preventable by the presence of monitoring systems. Although there are many systems widely in practice by disaster management agencies in monitoring flood levels, most of these systems are limited range and sophisticated to be used and maintained. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…To get accurate results, ultrasonic or proximity sensors must be installed or placed close or in 508 contact with the water surface. If the device is submerged or exposed to water, the sensor will be damaged and cannot work anymore [5]. A comprehensive review has shown that camera sensors are much better and more stable in detecting floods [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To get accurate results, ultrasonic or proximity sensors must be installed or placed close or in 508 contact with the water surface. If the device is submerged or exposed to water, the sensor will be damaged and cannot work anymore [5]. A comprehensive review has shown that camera sensors are much better and more stable in detecting floods [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to develop automatic water level detection systems using various approaches i.e. water surface, the water surface of velocity, and indicator level [4], [5]. The filtering approach is one of the more familiar methods for detecting water surfaces for flood detection [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%